1995
DOI: 10.2135/cropsci1995.0011183x003500040024x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and Nitrogen Supply during Seed Filling and Leaf Senescence in Soybean

Abstract: Leaf senescence and N redistribution during seed fdiing may limit soybean [Glycine max (L.) Merr.] yield by restricting the seed filling period. Experiments were conducted in the field and greenhouse to evaluate the relationship between seed N demand and leaf senescence. Plants (cv. McCall) were grown under shade cloth (which reduced insolation by 63%) from R1 to R$ (beginning seed fill), then the shade was removed from some plants with the objective of increasing photosynthesis, seed dry matter, and N accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 0 publications
3
19
0
1
Order By: Relevance
“…However, previous efforts to supply N during seedfill did not prevent senescence or N redistribution (Egli et al, 1978a;Hayati et al, 1995Hayati et al, , 1996. Likewise, in a comparison of soybean maturity isolines, a maturity group (MG) 6 isoline had 73 to 100% more total N at the beginning of seedfill than the MG 4 isoline but N content in harvested seed was not different (Mastrodomenico and Purcell, 2012), indicating that N supply was not limiting yield.…”
Section: Crop Nitrogen Dynamicsmentioning
confidence: 91%
See 1 more Smart Citation
“…However, previous efforts to supply N during seedfill did not prevent senescence or N redistribution (Egli et al, 1978a;Hayati et al, 1995Hayati et al, , 1996. Likewise, in a comparison of soybean maturity isolines, a maturity group (MG) 6 isoline had 73 to 100% more total N at the beginning of seedfill than the MG 4 isoline but N content in harvested seed was not different (Mastrodomenico and Purcell, 2012), indicating that N supply was not limiting yield.…”
Section: Crop Nitrogen Dynamicsmentioning
confidence: 91%
“…Others also observed that N deficiency shortened the EFP and accelerated leaf senescence (Boon-Long et al, 1983;Hayati et al, 1995). The self-destruct hypothesis also explains why a lower DMAC (or ISGR) increases the EFP by slowing the daily demand for C and N remobilization (Salado-Navarro et al, 1986a, 1986b, 1993.…”
Section: Crop Nitrogen Dynamicsmentioning
confidence: 96%
“…Properties of nuclei and cytoplasm in the line that stayed green, the transport of abscisic acid from pods to leaves, the accumulation of abscisic acid in leaves, and the translocation of nitrogen from leaves to pods were suggested as explanations for role of the above-ground parts of plants that was related to senescence (Guiamet et al, 1990;Nooden, 1984;Hayati et al, 1995). Delayed maturation of the stems of the Tachinagaha cultivar is observed in Tokyo and Chiba, namely, the southern parts of the Kanto district, but it is scarcely observed in northern areas, Nagano and Tochigi.…”
Section: Methodsmentioning
confidence: 99%
“…A number of researchers have attempted to identify critical periods for soybean yield determination (Egli, 1988; Board and Harville, 1993; Hayati et al, 1995; Board et al, 1996). Investigations on the vegetative period have reported no evidence to link either DM accumulation during the vegetative period or the duration of this period with yield (Weber et al, 1966; Egli, 1993).…”
mentioning
confidence: 99%